2021
DOI: 10.3390/diagnostics11060949
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs-1299, -126-3p and -30e-3p as Potential Diagnostic Biomarkers for Prediabetes

Abstract: This cross-sectional study investigated the association of miR-1299, -126-3p and -30e-3p with and their diagnostic capability for dysglycaemia in 1273 (men, n = 345) South Africans, aged >20 years. Glycaemic status was assessed by oral glucose tolerance test (OGTT). Whole blood microRNA (miRNA) expressions were assessed using TaqMan-based reverse transcription quantitative-PCR (RT-qPCR). Receiver operating characteristic (ROC) curves assessed the ability of each miRNA to discriminate dysglycaemia, while mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…22 MicroRNA-192 and -193b are reported to be significantly higher in pre-diabetes stage and return to lower levels following exercise. 23 The majority of microRNAs reported to be dysregulated in pre-diabetes through these studies [20][21][22][23] are also seen to be differentially expressed in our analysis (including miR-30e, miR-223, miR-126, miR-150 and miR-193b) (Fig. 1B).…”
Section: Discussionmentioning
confidence: 69%
“…22 MicroRNA-192 and -193b are reported to be significantly higher in pre-diabetes stage and return to lower levels following exercise. 23 The majority of microRNAs reported to be dysregulated in pre-diabetes through these studies [20][21][22][23] are also seen to be differentially expressed in our analysis (including miR-30e, miR-223, miR-126, miR-150 and miR-193b) (Fig. 1B).…”
Section: Discussionmentioning
confidence: 69%
“…Although increasing studies have been performed to examine the potential associations of miR-126 and miR-122 expression with T2DM and related glucose metabolism parameters, inconsistent results of existing studies remained. For example, evidence has shown a lower expression level of miR-126 in prevalent T2DM compared with healthy controls (6,11,17), whereas one recent study published in 2021 indicated that miR-126-3p was positively associated with T2DM risk and higher FBG level (18). Therefore, this meta-analysis systematically and quantitatively evaluated the relationship between circulating miR-126 and miR-122 expression levels and the risks of T2DM as well as related glucose metabolism parameters.…”
Section: Relationship Of Mirna-126 and Mirna-122 Expression With Type...mentioning
confidence: 97%
“…This miRNA is highly enriched in endothelial cells and is important for angiogenesis and wound repair [ 107 ]. It is down-regulated in T2D patients compared to non-diabetic controls and those with impaired glucose tolerance [ 62 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. It is also further down-regulated in T2D patients with complications [ 111 , 115 , 119 ] and increases after six months of treatment (insulin with diet control and exercise) [ 116 ].…”
Section: Epigenomics Biomarkers For T2dmentioning
confidence: 99%